2023
DOI: 10.1038/s41598-023-29700-y
|View full text |Cite
|
Sign up to set email alerts
|

On the forecastability of food insecurity

Abstract: Food insecurity, defined as the lack of physical or economic access to safe, nutritious and sufficient food, remains one of the main challenges included in the 2030 Agenda for Sustainable Development. Near real-time data on the food insecurity situation collected by international organizations such as the World Food Programme can be crucial to monitor and forecast time trends of insufficient food consumption levels in countries at risk. Here, using food consumption observations in combination with secondary da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Martini et al (2022) employed XGBoost, explaining up to 81% of the variation in insufficient food consumption and up to 73% of the variation in crisis or above food-based coping levels. The research by Foini et al (2023) demonstrated that precise forecasts of insufficient food consumption levels could be made up to 30 days into the future, thereby informing decisions regarding the allocation of need-based humanitarian assistance. However, Deléglise et al (2020) discovered that predicting food security indices is a challenging issue; their models did not exceed R 2 = 0.38 for the Household Dietary Diversity Score (HDDS) and R 2 = 0.35 for the Food Consumption Score (FCS).…”
Section: Discussionmentioning
confidence: 99%
“…Martini et al (2022) employed XGBoost, explaining up to 81% of the variation in insufficient food consumption and up to 73% of the variation in crisis or above food-based coping levels. The research by Foini et al (2023) demonstrated that precise forecasts of insufficient food consumption levels could be made up to 30 days into the future, thereby informing decisions regarding the allocation of need-based humanitarian assistance. However, Deléglise et al (2020) discovered that predicting food security indices is a challenging issue; their models did not exceed R 2 = 0.38 for the Household Dietary Diversity Score (HDDS) and R 2 = 0.35 for the Food Consumption Score (FCS).…”
Section: Discussionmentioning
confidence: 99%
“…Socio-economic variables, which are crucial for understanding vulnerabilities and impacts, are often limited to coarse administrative levels and infrequent sampling intervals. Nevertheless, ML can successfully leverage them to predict drought impacts in the Horn of Africa: the WFP HungerMap utilizes XGBoost regression-tree models 74 to nowcast 75 and forecast 76 food insecurity. In socioeconomic models, interpretability is crucial to generate trust from decision makers.…”
Section: Addressing the Current Limitations With Existing Ml: Opportu...mentioning
confidence: 99%
“…Near real-time data on the food insecurity situation collected by international organizations such as the World Food Programme can be crucial to monitor and forecast time trends of insufficient food consumption levels in countries at risk. 28 Another study found that food insecurity has been…”
Section: Food Insecuritymentioning
confidence: 99%